Advanced technology for gait rehabilitation: An overview - Tadeusz Mikolajczyk; Ileana Ciobanu; Doina Ioana Badea; Alina Iliescu; Sara Pizzamiglio; Thomas Schauer; Thomas Seel; Petre Lucian Seiciu; Duncan L Turner; Mihai Berteanu (Advances in Mechanical Engineering, 2018)
Most gait training systems are designed for acute and subacute neurological inpatients. Many systems are used for relearning gait movements (nonfunctional training) or gait cycle training (functional gait training). Each system presents its own advantages and disadvantages in terms of functional outcomes. However, training gait cycle movements is not sufficient for the rehabilitation of ambulation. There is a need for new solutions to overcome the limitations of existing systems in order to ensure individually tailored training conditions for each of the potential users, no matter the complexity of his or her condition. There is also a need for a new, integrative approach in gait rehabilitation, one that encompasses and addresses all aspects of physical as well as psychological aspects of ambulation in real-life multitasking situations. In this respect, a multidisciplinary multinational team performed an overview of the current technology for gait rehabilitation and reviewed the principles of ambulation training.